Mechanisms of Dye Incorporation into Potassium Sulfate: Computational and Experimental Studies - Carter, Damien; Ogden, Mark; Rohl, Andrew (American Chemical Society, 2007)
Potassium sulfate crystals orient and overgrow 2-aminobenzenesulfonate (OSA), and many other sulfonated aromatic compounds, on particular facets during growth from solution. The energetics associated with adsorption of OSA and benzenesulfonate (BS) were calculated using both molecular mechanical and density functional methods, in order to assess the surface binding effectiveness of these compounds on various faces of potassium sulfate. It was found that both theoretical techniques predicted that OSA and BS bind to potassium sulfate to a similar extent. The surface binding capacities were also assessed experimentally by studying the growth rates of individual faces of K2SO4, with results showing similar findings to those from the computational studies.